Kinematic analysis of volleyball attack in the net center with various types of take-off - Zahalka, F.; Maly, T.; Mala, L.; Ejem, M.; Zawartka, M. (Journal of Human Kinetics, 2017)
The aim of the study was to describe and compare kinematics in two types of execution of attack hit, the goofy approach and regular approach. The research group consisted of players from the Czech Republic`s top league (n = 12, age 28.0 ± 4.3 years, body height 196.6 ± 5.6 cm, body mass 89.7 ± 6.7 kg) divided into two groups according to the individual type of approach in the attack. Analysis of movement was performed by 3D kinematics video analysis, space coordinates were calculated by the DLT (Direct Linear Transformation) method together with interpretation software TEMA Bio 2.3 (Image Systems AB, Sweden). The players started their run-up from a distance of about 4 - 4.5 m from the net with similar maximal vertical velocity (2.91 - 2.96 m·s-1). The trajectory of players with goofy approach seemed to be convenient for the rotation of shoulders and hips in the moment of ball contact. Differences between both groups were observed. Players with a goofy approach had a longer flight phase compared to regularly approaching players.